Pediatric Crohn's disease presenting with a large calcified pelvic mass - Dominic C. Grimberg, BS; Lung W. Lau, MD; Wissam Dahoud, MD; Spencer Couturier, MD; Raymond W. Redline, MD; Anne C. Kim, MD MPH (Elsevier, 2017)
Small bowel Crohn's disease classically presents with symptoms of abdominal pain, diarrhea, and weight loss in the pediatric population. However, there is no published literature on its presentation associated with a dystrophically calcified pelvic mass. We present a case of a 15-year-old female presenting with four weeks of inflammatory bowel disease (IBD) symptoms as well as a large calcified pelvic mass suggestive of chronic, organized inflammatory process versus a calcifying fibrous tumor.